PENGARUH MODAL SENDIRI TERHADAPSHU PADA KPRI TIRTA MANUNGGAL SEJAHTERABALAI PUSDA & TARU PROBOLO KUTOARJO (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
This study aims to determine the extent to which the influence of own capital against the SHU in Koperasi Pegawai Negeri (KPRI) Tirta Manunggal Sejahtera Balai Pusda and Taru Probolo Kutoarjo fiscal year 2012 - 2016. This research uses quantitative and qua litative data analysis methods with simple regression analysis tool, Determination, Test f and T test. The result of the research by using SPSS program showed that there is a positive and significant influence between the Deposit and Mandatory Deposit vari able on the change of SHU in KPRI Tirta Manunggal Sejahtera where Y =-1.061 - 0,253x1 + 0,17x2, seen from the value of the constant coefficient of 1.061 which has meaning when the Deposit and Mandatory Saving is equal to zero (0) units then SHU is - 1,061. The Basic Deposit Value is the coefficient of linear regression direction which means that each increase of Staple Deposit by 1 unit while Deposit Mandatory is considered fixed, it will be followed by SHU decline.Mandatory Deposit Value of 0.17 is a coefficient of linear regression direction which means the increase of Mandatory Deposit by 1 unit while the Main Deposit is considered fixed, it will be followed by a SHU increase of 0.17. Similarly, based on the value of f arithmetic and f value tables that ha ve been in can, f arithmetic> ftable or 78.74> 19.00 then this means that HO rejected and H3 accepted in other words that simultaneously there is a positive and significant influence between dependent variable of Main Deposit and Deposit to the change of SHU in KPRI Tirta Manunggal Sejahtera for the last 5 years. The amount of own capital derived from Deposit Principal and Compulsory Deposit is a strong influence on the SHU means that the greater the capital itself the greater the acquisition of SHU.